EFFECT OF HIGH PRESSURE COOLANT JET ON CUTTING TEMPERATURE, TOOL WEAR AND SURFACE FINISH IN TURNING HARDENED (HRC 48) STEEL (Journal of Mechanical Engineering, 2015)
Hard turning of harder material differs from conventional turning because of its larger specific cutting forces requirements. The beneficial effects of hard turning can be offset by excessive temperature generation which causes rapid tool wear or premature tool failure if the brittle cutting tools required for hard turning are not used properly. Under these considerations, the concept of high-pressure coolant (HPC) presents itself as a possible solution for high speed machining in achieving slow tool wear while maintaining cutting forces at reasonable levels, if the high pressure cooling parameters can be strategically tuned. This paper deals with an experimental investigation of some aspects of the turning process applied on hardened steel (HRC48) using coated carbide tool under high-pressure coolant, comparing it with dry cut. The results indicate that the use of high-pressure coolant leads to reduced surface roughness, delayed tool flank wear, and lower cutting temperature, while also having a minimal effect on the cutting forces.